2017
DOI: 10.1016/j.resuscitation.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside enhanced cardiopulmonary resuscitation improves short term survival in a porcine model of ischemic refractory ventricular fibrillation

Abstract: Introduction Sodium nitroprusside (SNP) enhanced CPR (SNPeCPR) demonstrates increased vital organ blood flow and survival in multiple porcine models. We developed a new, coronary occlusion/ischemia model of prolonged resuscitation, mimicking the majority of out-of-hospital cardiac arrests presenting with shockable rhythms. Hypothesis SNPeCPR will increase short term (4-hour) survival compared to standard 2015 Advanced Cardiac Life Support (ACLS) guidelines in an ischemic refractory ventricular fibrillation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…This would likely limit the observed effectiveness of ECMO. Prior studies performing standard ACLS in this same model of ischemic VF have demonstrated a low ROSC rate, suggesting a minimal impact in this study (3) . This may also eliminate the injury typically caused by repeated defibrillation in clinical situations.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This would likely limit the observed effectiveness of ECMO. Prior studies performing standard ACLS in this same model of ischemic VF have demonstrated a low ROSC rate, suggesting a minimal impact in this study (3) . This may also eliminate the injury typically caused by repeated defibrillation in clinical situations.…”
Section: Discussionmentioning
confidence: 75%
“…We used 33 pigs with an average weight of 44 ± 3 kg. The surgical preparation under aseptic conditions, anesthesia, data monitoring, and recording procedures used in the present study have been described elsewhere 3 , 4 , 5 . Briefly, pigs were anesthetized with intramuscular ketamine (1,000 mg) followed by inhaled isoflurane at a dose of 0.8% to 1.2%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the primarily vascular activity, it may also have antioxidant effects through the release of NO, which is a potent antioxidant and is capable of rendering neuroprotection against oxidative stress-induced neurotoxicity [23]. Besides nitroglycerin, sodium nitroprusside-enhanced CPR has been shown to improve myocardial, carotid, and cerebral blood flow, postresuscitation left ventricular global function, and 24-h survival with good neurological function in porcine models of cardiac arrest [24,25]. Also, the addition of inhaled NO to hemodynamic-directed CPR may improve short-term survival and intra-arrest hemodynamics [26].…”
Section: Improving Microcirculatory Blood Flowmentioning
confidence: 99%